Bond strength and Raman analysis of the zirconia-feldspathic porcelain interface - Borges, Ana Flávia Sanches; Ramos, Carla Muller; Mondelli, Rafael Francisco Lia; Cesar, Paulo; Tabata, Américo Sheitiro [UNESP]; Santos, Juliete de Souza (Elsevier, 2014)
The test groups were experimental zirconia, Zirkonzahn zirconia, and Schuetz zirconia. Blocks of partially sintered zirconia were cut into disks (n=20) and then veneered with a feldspathic porcelain. Half of the specimens from each group (n=10) were incubated in 37°C water for 24 hours, and the other half were thermocycled. All the specimens were then subjected to shear testing. The fractured areas were analyzed with optical stereomicroscopy and classified as adhesive, cohesive, or an adhesive-cohesive failure. Spectral patterns were examined to detect bands related to the zirconia and feldspathic porcelain phases. The shear strength data were submitted to 2-way ANOVA. Results No significant differences in shear bond strength were observed among the 3 groups, regardless of whether or not the specimens were thermocycled. Adhesive failures were the most prevalent types of failure (70%). Raman spectra were clearly distinguished for all the materials, which showed the presence of tetragonal and monoclinic phases. Conclusions The controlled production of the experimental zirconia did not influence the results of the bond strength. Raman analysis suggested a process of interdiffusion by the presence of peaks associated with the zirconia and feldspathic ceramics.